Penrapan Metode TOPSIS dalam Pentuan Prioritas Suplier Bahan Baku Pada Perusahaan Manufaktur Obat - Julio Warmansyah; Yoga Syahrul Ramadhan (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2022)
Determination of suppliers in the process of filling raw materials in the warehouse is very important for a company. Various types of companies will depend on the supply of raw materials such as production companies. A decision support system is needed to help make decisions in determining raw materials that have various criteria. Evaluation of suppliers is very important to get the right supply of raw materials. Things to consider in determining raw materials are the quality of the raw materials supplied to the company, competitive prices with other competitors, so that it is expected to produce products that have affordable cost of production, delivery in the fulfillment of raw materials continuously to support production, services provided by suppliers in the process of supplying raw materials to the company, offers of raw materials provided by suppliers in filling raw material needs.